Benefits and burdens of rural development : some public policy viewpoints - Iowa State University (Ames : Iowa State University Press, 1970)
This volume presents the papers and formal discussions of a seminar sponsored by the Iowa Centre in May l969. Sixteen papers are subsumed under the headings of "Some General Economic and Social Characteristics of Rural Communities, 2' "Effects of the Stage of Growth and Technology on Rural Communities," "Economic and Social Policies for Improvement of Rural Living," and "Public Policies to Relate Welfare of Rural People to National Goals."
Papers of a seminar sponsored by the Iowa State University Center for Agricultural and Economic Development, May, 1969.
Includes index
Includes bibliographical references .
lje 24/01/2018
Loans
Keywords: Rural conditions; Agriculture and state; United States